Effect of pumping and spraying processes on the rheological properties and air content of wet-mix shotcrete with various admixtures. (20th November 2019) - Chen, Lianjun; Ma, Guanguo; Liu, Guoming; Liu, Zhaoxia
Graphical abstract: Effect of alternative thrust (shock) and shear on concrete flow in pipes. Highlights: Effect of pump and spray process on rheology of concrete was investigated. Mechanism of pump and spray process affecting concrete rheology was expounded. Prediction models of the changes of concrete performance were built. Influence degree of wet-mix shotcrete process on concrete rheology was analyzed. Abstract: Wet-mix shotcrete mainly includes two processes: pumping and spraying. In this study, to explore the effects of the pumping and spraying processes on the rheological properties and air content of concrete, a full-scale experimental system of wet-mix shotcrete was developed with the given work parameters of these processes. The rheological parameters, slump, and air content of the fresh concrete were measured before pumping, after pumping, and after spraying, respectively. In general, the air content decreased after pumping, whereas the flow resistance declined after pumping and then increased after spraying. These changes were linked to the shear and shock caused by the pumping or spraying process. Under the interference of the pumping and spraying processes, prediction models of the changes in concrete properties were developed. Finally, a one-way analysis of variance (ANOVA) was conducted to analyze the degree of influence of the pumping and spraying processes on concrete properties. This work could be beneficial for further improvement of the understanding of the overall wet-mix shotcrete material and processes.